Impact of Yogyakarta International Airport (YIA) Development on the Livelihood Assets of Self-Managed Relocation Communities in Temon Sub-District, Kulon Progo Regency - Fathunnafi, Avicenna; Surjono; Wijayanti, Wawargita Permata (Journal of Regional and Rural Studies, 2025)
The development of Yogyakarta International Airport (YIA) has transformed agricultural land and forced community relocation, impacting villagers who primarily rely on agriculture. This study evaluates the impact of the development on community livelihood capitals, covering natural, physical, human, financial, and social capitals. Using a descriptive quantitative approach, data were collected through a primary survey with questionnaires involving 74 household heads in self-managed relocation sites as samples. The self-managed relocation group was chosen as it represents the largest affected group (54.6%). Pentagon Assets analysis and the Wilcoxon Signed Rank Test were applied to measure significant changes in livelihood capitals 8 years post-airport development. Findings reveal a sharp decline in natural capitals due to land conversion, with 55.41% of the community losing agricultural land and 58.11% facing a decrease in water quality.. Financial and social capitals also deteriorated due to reduced income, limited loan access, and weakened farming community bonds. Conversely, physical and human capitals improved, supported by compensation funds for infrastructure and better education access. However, rising land values have made it difficult for communities with limited compensation, pushing them toward informal employment. Thus, YIA’s development has significantly negatively impacted natural, financial, and social capitals, despite slight improvements in physical and human capitals.